Microstructural properties and wear behaviour of AlSi9Mg matrix B4Cp reinforced composites - Toptan, Fatih; Kerti, Isil; Sagin, Ahmet; Cigdem, Mustafa; Daglilar, Sibel; Yuksel, Fatih (JOHN WILEY & SONS, 2011)
In the present work, AlSi9Mg alloy matrix composites reinforced with 10, 15 and 20% (wt.) B4Cp were produced by casting route at 850 degrees C. Titanium-containing flux (K2TiF6) was used to overcome the wetting problem between B4C and liquid aluminium metal. The microstructure of matrix/reinforcement interfaces were investigated with SEM studies. The reaction layer was also characterized with EDS analysis and X-ray mapping. It was found from the microstructural observations by high resolution field emission gun SEM (FEG-SEM) that the wetting improved by the formation of very thin (80-180 nm in thickness) TiC and TiB2 reaction layers. The samples were subjected to pin-on-disc wear tests against AISI 4140 pin under dry sliding conditions. The worn surface was studied through SEM and EDS analysis. It has seen that, wear resistance increased as particle volume fraction increased.
Keywords: Aluminium; Boron carbide; Casting; Composite; Interface; Microstructure; Wear; ALUMINUM; PARTICLES; NICKEL; Materials Science